Peran Motivasi Belajar Dalam Memoderasi Pemahaman Perpajakan, Intensitas Pemberian Tugas, Dan Kebiasaan Belajar Terhadap Hasil Belajar Akuntansi Perpajakan - Parni Parni; Agung Listiadi (Jurnal Pendidikan Ekonomi)
The research aims to analyze whether there is an influence of understanding taxation, intensity of assignment, and study habits on tax accounting learning outcomesby  partial, to analyzy whether there is an influence of understanding taxation, intensity of assignment, and study habits on tax accounting learning outcomes partially moderated by learning motivation variables. The type of research is quantitative research. The sampling technique used purposive sampling  with a total of 176 respondents. Data collection techniques using and documentation and questionnaire. The data analysis technique use SEM (Structural Equation Modeling) analysiswith WarpPLS approach. The results showed that understanding of taxation, intensity of assignments and habits had a significant effect on tax accounting learning outcomes partially. Learning motivation is a moderating variable of understanding taxation on tax accounting learning outcomes. Learning motivation is not a moderating variable of the intensity of assignments to tax accounting learning outcomes. Learning motivation is a moderating variable of study habits towards tax accounting learning outcomes.DOI: https://dx.doi.org/10.17977/UM014v13i22020p165